СТРАТИГРАФИЧЕСКОЕ РАСПРОСТРАНЕНИЕ ПАЛЕОЗОЙСКИХ МШАНОК МОНГОЛИИ - Я. АРИУНЧИМЭГ (Geological Issues, 2023)
Bryozoa is one of the widespread invertebrate fossils in the Paleozoic of Mongolia. This article presents the new data obtained on the study of Paleozoic Bryozoa in Mongolia during the activity of Soviet-Mongolian Paleontological Joint Expedition. At that time from 13 Ordovician, 32 Silurian, 90 Devonian, 48 Carboniferous and 31 Permian localities were described 225 species of Bryozoa. The following 21 assemblages of Bryozoa as well as their distribution and biostratigraphic succession are analyzed: Upper Caradocian, Ashgillian (Ordovician); Llandoverian-Wenlockian, Wenlocian, Ludlovian- Pridolian, Pridolian (Silurian); Early Devonian, Eifelian, Givetian, Givetian-Frasnian and Famennian (Devonian); Early Turnesion, Late Tiimesian, Early Visean, Middle Visean, Late Visean-Serpuchovian, Scrpuchovian and Bashkiria!! (Carboniferous); Sakinarian-Artinskian, Roadian and Capitanian (Permian).